2017
DOI: 10.1186/s12868-017-0347-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of skilled reaching training and enriched environment on generation of oligodendrocytes in the adult sensorimotor cortex and corpus callosum

Abstract: Background Increased motor activity or social interactions through enriched environment are strong stimulators of grey and white matter plasticity in the adult rodent brain. In the present study we evaluated whether specific reaching training of the dominant forelimb (RT) and stimulation of unspecific motor activity through enriched environment (EE) influence the generation of distinct oligodendrocyte subpopulations in the sensorimotor cortex and corpus callosum of the adult rat brain. Animals were placed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 57 publications
(94 reference statements)
2
25
0
Order By: Relevance
“…4B, p=0.04) compared to SH controls. This finding is 270 concordant with previous observations of enhanced differentiation following activity-271 dependent stimulation (Cullen et al, 2019;Gibson et al, 2014;Hughes, Orthmann-Murphy, 272 Langseth, & Bergles, 2018;Keiner et al, 2017;Mitew et al, 2018;Xiao et al, 2016). 273…”
supporting
confidence: 86%
See 1 more Smart Citation
“…4B, p=0.04) compared to SH controls. This finding is 270 concordant with previous observations of enhanced differentiation following activity-271 dependent stimulation (Cullen et al, 2019;Gibson et al, 2014;Hughes, Orthmann-Murphy, 272 Langseth, & Bergles, 2018;Keiner et al, 2017;Mitew et al, 2018;Xiao et al, 2016). 273…”
supporting
confidence: 86%
“…However, these artificial 28 methods to upregulate neuronal stimulation to promote myelin plasticity may be 29 problematic, as they may not actually reflect physiological levels of stimulation and have 30 recently been shown to promote the progression of tumor growth (Venkataramani et al, 31 2019;Venkatesh et al, 2019). Interestingly, young adult mice (Xiao et al, 2016) and rats 32 (Keiner et al, 2017) that were taught complex motor paradigms exhibited an increase in 33 new OL production, suggesting that OL adaptability extends to adulthood and is 34 physiologically relevant. While these findings are exciting, a complete understanding of the 35 precise changes in cellular dynamics induced by physiologically relevant stimulation and 36 how this ultimately influences myelin in the adult CNS remains unknown.…”
Section: Introduction (4428 Characters)mentioning
confidence: 99%
“…Taken together these results provide the first evidence that MTR is sensitive to longitudinal changes in myelin in white matter. While previous studies have focused on the motor cortex, where a higher number of recently differentiated oligodendrocytes are found after motor learning 42,43 , here, using a whole-brain approach, we detected MTR increases in S1 and S2, and a trend in cerebellum, suggesting increases in myelination in these areas as well.…”
Section: Discussionsupporting
confidence: 41%
“…Myelin plasticity could potentially be achieved by increased differentiation of OPCs, as well as changes in thickness, number and/or length of sheaths (Fields, 2015). Experiments have shown that experiences such as enriched environment and learning can induce such changes (Blumenfeld-Katzir et al, 2011;Sampaio-Baptista et al, 2013;Keiner et al, 2017) that can be indirectly detected with MRI in humans (Scholz et al, 2009;Sagi et al, 2012;Hofstetter et al, 2013).…”
Section: Introductionmentioning
confidence: 99%